A Systematic Review: Mobile Application Monitoring Post Operation Caesarean Section - Zahrotul Widad; Ninuk Dian Kurniawati; Kristiawati Kristiawati (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
Introduction: Surgical wound infection (ILO) is a serious complication and can cause significant morbidity, including increasing the risk of readmission and prolonging recovery time.Objective: To review the effect of mobile apps to improve the quality of post-operative care by reducing the need for physical visits and increasing remote supervision.Methods: The literature search used 5 databases: Cinahl, Proquest, Pubmed, Scopus, and ScienceDirect in 2017-2024. The articles selected were original research RCT and cohort, English language, containing postoperative sectio caesarea, and using an application. The keywords used were: Telehealth OR Mobile Application OR application OR app AND Wound Monitoring OR wound care AND Cesarean Section OR Cesarean Section. In assessing research bias using the Critical Appraisal Skills Program (CASP) and the Joanna Briggs Institute (JBI) obtained a score of 77-100%.Results: Surgical wound infection (SSI) is a serious complication that can increase morbidity and prolong recovery time after caesarean. Of the 196 articles that were found, seven met the inclusion criteria and were further analyzed. Results suggest that mobile apps can track wound conditions in real-time, reduce the need for physical visits, and increase patient engagement in the care process. These findings suggest that mobile apps can detect early signs of infection and educate patients, supporting faster and more effective recovery.Conclusions: The use of mobile apps can reduce financial burden, support home visit integration, reduce economic barriers and improve health outcomes.